Pengelolaan Desa Wisata Adat Ngadas Berbasis Masyarakat Adat - Annabel Carlene Claresta; Velicya Tarisha Cheung; Stanley Gracius Christoper; Steven Ryan Tedja; Budi Setiawan (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2024)
This research examines the management of indigenous community-based tourism villages in Ngadas Village, Poncokusumo District, Malang Regency, East Java. Ngadas Tourism Village offers significant tourism potential by maintaining local customs and culture, as well as pristine natural beauty. In its management, the local community, together with the Tourism Awareness Group (POKDARWIS), plays an active role in various activities such as homestay management, special vehicle rental to get to Bromo Crater, as well as preservation of culture and the surrounding environment. The purpose of the study was to determine the management of the Ngadas Indigenous Tourism Village based on Indigenous Peoples. Research on the indigenous community-based Ngadas traditional tourist village uses a descriptive qualitative method that uses data collection techniques through interviews and observations in the field. The result of this research is that Ngadas Tourism Village has homestay and guesthouse facilities managed by the local community, as well as serving culinary specialties such as corn rice. The village also maintains traditions such as the Bantengan dance and the entas-entas ceremony, as a tourist attraction. Tourism village management that involves local communities not only has a positive impact on economic aspects, but also helps preserve culture and the environment. In conclusion, effective tourism village management in Ngadas Village prioritizes local community empowerment, environmental sustainability, and cultural preservation, which are the main attractions for tourists.